Effect of oxygen partial pressure on the composition and structure of GdBa2Cu3O7−δ by solid state reaction. (December 2015) - Tu, R.; Ke, W.; Zhang, S.; Wang, T.; Zhang, L. M.; Goto, T.
Abstract : GdBa2 Cu3 O7− δ (GdBCO or Gd123) ceramics have been successfully prepared at oxygen partial pressure ( ) of 0.02–0.10 MPa via solid state reaction method by using Gd2 O3, BaCO3 and CuO powders as raw materials, whereas GdBa2 Cu3 O7− δ decomposed to Gd2 BaCuO5 (Gd211), Gd2 O3 and barium copper oxides owing to the instability of GdBa2 Cu3 O7− δ at according to the stability phase diagram of GdBa2 Cu3 O7− δ . Effect of on the phase structure and microstructure of GdBa2 Cu3 O7− δ has been investigated by X-ray diffractometer and field-emission scanning electron microscopy methods. Composition and microstructure of pellets sintered at were totally different from pellets sintered at .